Formulation Of Visual Narrative Reading And Coding Approach Through Cultural Waterfront Portraiture Photographs Analysis - Musa, Eddy Izuwan (2021)
Present Visual Narratology almost exclusively encompass images in motion or sequential images despite some dialectics arguing the possibility of extending to single, still frame images. Inversely, present Visual Semiotics encompassing singular, still frame images share a proclivity for culturally-informed interpretations but do not constitute a Narratological perspective. Alongside these issues, the narrative-ability of single still frame images are also being contested. To address these gaps and inconsistencies, the study examines the possibility of a systematic narrativization from the reading of single, still-frame images. It performs its premise by formulating a systematic Visual Narrative Reading and Coding Approach constituting a simultaneous theoretical appropriation of Visual Narratology and Visual Semiotics deployed through a Qualitative Method Design with Visual Coding. Through this systematic approach, any projected narrative rhetoric output would be comprehensive and ethnographically informed of its key Protagonist’s World circumstances while simultaneously be grounded by evidential data deduced from the image’s visual signifiers. The approach’s deployment is demonstrated on selected photographs featuring Waterfront communities, resulting in systematic narrative rhetoric outputs. This led to its overall findings that assert a systematic narrativization of single still image is possible, despite being read independently from any accompanied mediums such as captions, audio or inferred temporality.